2019
DOI: 10.4103/jrpp.jrpp_18_78
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of Vitamin C intracoronary administration in preventing cardiac injury after primary percutaneous coronary intervention in patients with ST-elevation myocardial infarction

Abstract: Objective: The aim of the present study was to determine the effects of intravenous (IV) and intracoronary administration of Vitamin C on the incidence of periprocedural myocardial injury in patients undergoing primary percutaneous coronary intervention (PCI). Methods: In this prospective, double-blind, randomized clinical trial, that was conducted in Tehran Heart Center, Iran, between October 2016 and March 2017, 252 patients undergoing primary PCI were enrolled to rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…After restoring blood flow with PCI, several studies have shown an elevation of troponins and increased CK-MB. Treatment with Vit C reported positive outcomes for reducing troponin and CK-MB levels, although the results are conflicting as others studies failed to show a benefit [ 9 , 73 ].…”
Section: Cardioprotection By Vitamin Cmentioning
confidence: 99%
See 1 more Smart Citation
“…After restoring blood flow with PCI, several studies have shown an elevation of troponins and increased CK-MB. Treatment with Vit C reported positive outcomes for reducing troponin and CK-MB levels, although the results are conflicting as others studies failed to show a benefit [ 9 , 73 ].…”
Section: Cardioprotection By Vitamin Cmentioning
confidence: 99%
“…One of the therapies used to reduce the infarct size is Vit C due to its capacity to act as a ROS scavenger and reduce oxidative stress. Moreover, it can confer cardioprotection [ 73 ]. However, another study has shown that Vit C, given prior to reperfusion at enough dosing to reach plasma levels over 10 mmol/L, did not show a significant difference in infarct size [ 69 ].…”
Section: Cardioprotection By Vitamin Cmentioning
confidence: 99%